Human friendly mechatronics selected papers of the International Conference on Machine Automation : ICMA 2000 : September 27-29, 2000, Osaka, Japan - Arai, Eiji, 1953-; Arai, Tatsuo; Takano, Masaharu
Includes 61 selected papers from 106 presented at the second International Conference on Machine Automation (ICMA2000). This book offers the information on: Human Interface and Communication; Human Support Technology; Actuator and Control; Vision and Sensing; Robotics and Design; and, Manufacturing System.